Non-Price Competitivenes Factors in a Value Chain of a Tourism Product - GARASYMLIUK, Mariia; DANYLYSHYN, Bohdan; MARTYNIUK, Uliana; MAKAROVYCH, Viktoriia; POLIVODA, Olha; NEZVESHCHUK-KOHUT, Tetiana; POPADYNETS, Nazariy (Journal of Environmental Management and Tourism, 2023)
The paper addresses the detection and hierarchical composition of non-price factors influencing the quality of a tourism product in the environment of its value chain components from the viewpoint of the way the customers of travel companies understand these factors. The competitiveness dimensions are outlined for micro- and nanolevels, and the scheme to develop the competitive strategy based on the change of external environment factors is offered. The tourism product value chain scheme is generalized from the viewpoint of a travel company. The paper proves that the customers’ desire to maximize the value of a tourism product is based not only on the understanding of the acceptability of respective costs but also the level of awareness about the exclusiveness and quality of the infrastructural framework of the offer. The authors reveal that the components of the customers’ understanding of the tourism product value chain are related to the integral understanding of tourism service. The components of non-price factors are outlined chronologically and non-price factors of impact on the competitiveness in various links of the value chain are identified. The priority of inclusion was estimated by the rapid test method. The suggested hierarchy can foster the more qualitative ranging and updating of certain components of a tourism product to improve its understanding by customers, which will impact the competitive positions of the travel companies.